2015
DOI: 10.4236/ijcm.2015.63017
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Body Tumours: A Review

Abstract: The carotid body is a small structure weighing 12 mg located in the adventitia of carotid artery bifurcation acting as a chemoreceptor. Carotid body tumour (CBT); formerly known as chemodectoma is a rare, highly vascular, mostly benign tumour arising from the paraganglia of carotid body; hence, the name (carotid paraganglioma). The high vascularity and proximity to cranial nerves and major vessels make this tumour a surgical challenge. Abundant literature has been written about CBT in the last century with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Most of them are sporadic and about 10% of them are familial. Interestingly they are more frequent in population living in high altitudes and this has suggested that they represent an extreme form of hyperplasia of carotid sinus cells due to chronic hypoxia [ 59 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them are sporadic and about 10% of them are familial. Interestingly they are more frequent in population living in high altitudes and this has suggested that they represent an extreme form of hyperplasia of carotid sinus cells due to chronic hypoxia [ 59 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative definition of the anatomy with all possible radiological means, including computerized tomographic arteriography, seems a cardinal factor for success. Disease progression is usually slow allowing a good prognosis [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…[8] It consists of two types of cells: chief cells and sustentacular cells which are derived from neural crest cells and neuroectoderm, respectively. [9] The tumors arising from the chief paraganglial cells are termed as paragangliomas and accounts for about 0.5% of all tumors. It accounts for 1 out of 30,000 head and neck tumors cases with 65% occurring in the carotid body region and are termed as CBP.…”
Section: Discussionmentioning
confidence: 99%
“…The embryologic origin is from the third branchial arch and contains homeostatic chemoreceptor cells-the sensory nerve endings of the carotid sinus nerve penetrate the clusters to synapse with chemoreceptor cells [31][32][33][34][35][36][37]. The carotid body is made up of two types of cells, called glomus cells: glomus type I cells derived from the neural crest, and glomus type II cells and act as supporting cells [38][39][40][41][42][43][44][45][46][47]. The glomus or type I cells of the CB are the transducers of hypoxic stimuli, and relay chemosensory information to the brainstem via neurotransmitter release at synaptic contacts with afferent terminals of the carotid sinus nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that ligation of the external carotid artery provides a safe opportunity for operation in cases with larger tumors that are densely adherent to the carotid artery [45]. The ligation of the ICA must be avoided if possible because of the 66% prevalence of stroke [46]. The surgical technique must perform precise anatomic dissection and vascular control before the tumor excision.…”
Section: Treatment Optionsmentioning
confidence: 99%